Formation of nanostructured silicon surfaces by stain etching - Ayat, Maha (Nanoscale Res Lett, 2014)
In this work, we report the fabrication of ordered silicon structures by chemical etching of silicon in vanadium oxide (V(2)O(5))/hydrofluoric acid (HF) solution. The effects of the different etching parameters including the solution concentration, temperature, and the presence of metal catalyst film deposition (Pd) on the morphologies and reflective properties of the etched Si surfaces were studied. Scanning electron microscopy (SEM) was carried out to explore the morphologies of the etched surfaces with and without the presence of catalyst. In this case, the attack on the surfaces with a palladium deposit begins by creating uniform circular pores on silicon in which we distinguish the formation of pyramidal structures of silicon. Fourier transform infrared spectroscopy (FTIR) demonstrates that the surfaces are H-terminated. A UV-Vis-NIR spectrophotometer was used to study the reflectance of the structures obtained. A reflectance of 2.21% from the etched Si surfaces in the wavelength range of 400 to 1,000 nm was obtained after 120 min of etching while it is of 4.33% from the Pd/Si surfaces etched for 15 min.